Carotid Artery Angioplasty and Stenting: 2-Dimensional Operative Video. Issue 6 (16th November 2020) - Darwal, Maureen A; Liebman, Kenneth M; Binning, Mandy J
Abstract: Carotid artery angioplasty and stenting (CAS) has been shown to be equally effective as carotid endarterectomy (CEA) for carotid stenosis in both symptomatic and asymptomatic disease. 1 In patients who are considered high risk for endarterectomy, CAS is safe and effective. 2 While this is a common procedure, proper technique is crucial to ensure that the procedure is safe with minimal risk of stroke. This patient consented to treatment. The following is a video detailing the CAS procedure in a 77-yr-old male with a symptomatic 65% carotid stenosis (by NASCET criteria 3 ) in a patient with prior CEA.